Kalkkrusten und Kegelkarst - Pfeffer, Karl-Heinz (ERDKUNDE, 1969)
In SW Jamaica, three variants of cockpit-karst phenomena were observed in one karst area. 1. steep karst pillars, completely formed in firm white limestone, 2. steep karst pillars encrusted with external stalactites and travertine on bare rock interstices and over hangs, 3. karst hillocks and cockpits covered with weathering residues, including a limestone crust overlying decomposed limestone particles. Typical profiles were taken and samples of limestone crust and decomposed limestone particles subjected to laboratory analysis. Limestone crust occurences in humid tropical areas are described from the literature, theories of their origin discussed and types of formation investigated. The information gained by Panos and Stelcl in Cuba are examined for the Jamaican forms and the conclusion drawn that special conditions must operate in Cuba, since travertine and limestone crusts have no significant influence on forms in Jamaica. They are a humid-tropic variant of cockpit karst forms climatically and petrographically determined.